Analisis Pengaruh Gangguan Sistem Terhadap Kepuasan Nasabah: Studi Kasus Pada Bank Syariah Indonesia Dengan Pendekatan Manajemen Layanan Di Universitas Islam Kebangsaan Indonesia - Rauzana, Rauzana; Zikry, Farhan; Marisa, Laini; Farid, Diana (Yayasan Cendekia Gagayunan Indonesia, 2025)
System disruptions in Islamic banking can affect service quality and customer satisfaction. This study aims to analyze the impact of system disruption on customer satisfaction at Bank Syariah Indonesia at Universitas Islam Kebangsaan Indonesia (UNIKI). This research uses quantitative methods with a survey to customers who experience system disruptions. The results showed that disruptions such as transaction delays and difficulty accessing services can reduce customer satisfaction levels. However, responsive service management in handling complaints and fixing problematic systems can mitigate these negative impacts, maintain customer loyalty, and improve service quality. This study suggests the importance of improving system reliability and better service management in the context of Islamic banking in the university environment.